The soundscape, a theoretical approach from semiotics point of view (2015)
This review article focuses in the theory of Soundscape (developed by Canadian composer and music educator R. Murray Schafer), and its interpretation from semiotics. Initially, the relationship between people and Soundscape is reported in the essay. Subsequently, the semiotics is discussed as a discipline that explains the codes and its signs and their application to the sound phenomenon interpretation, besides mentioning some related works with the semiotics of music. Finally, it is considered important thinking how teens relate to their environment sound, concluding that the soundscape of any community is constantly changing due to technological and environmental facts. For this reason, connecting Soundscape to educational processes of students is necessary. Also, semiotics is a possibility for the explanation of the Soundscape, establishing itself as a source of potential research in music.